Cannabis sativa L.: Crop Management and Abiotic Factors That Affect Phytocannabinoid Production - Ingrid Trancoso; Guilherme A. R. de Souza; Paulo Ricardo dos Santos; Késia Dias dos Santos; Rosana Maria dos Santos Nani de Miranda; Amanda Lúcia Pereira Machado da Silva; Dennys Zsolt Santos; Ivan F. García-Tejero; Eliemar Campostrini (Agronomy, 2022)
The main characteristic of Cannabis sativa L. is the production of compounds of medicinal interest known as phytocannabinoids. Environmental factors and crop management practices are directly related to the yield of these compounds. Knowing how these factors influence the production of phytocannabinoids is essential to promote greater metabolite yield and stability. In this review, we aim to examine current cannabis agronomic research topics to identify the available information and the main gaps that need to be filled in future research. This paper introduces the importance of C. sativa L., approaching state-of-the-art research and evaluating the influence of crop management and environment conditions on yield and phytocannabinoid production, including (i) pruning; (ii) light and plant density; (iii) ontogeny; (iv) temperature, altitude, and CO2 concentration; (v) fertilization and substrate; and (vi) water availability, and presents concluding remarks to shed light on future directions.